Fatty acids analysis to differentiate nutritional quality of similar bakery products - Albuquerque, T.G. (2019)
Bakery products are a wide group of ready-to-eat processed foods, highly consumed, especially by young people. In the last years, increased attention has been dedicated to the intake of fat, focusing on the type of fat, namely saturated (SFA) and trans fatty acids. Margarine, butter, partially hydrogenated vegetable oils and shortening are the main fat sources used to produce bakery products. Therefore, it is of utmost importance to evaluate fatty acids profile of these products to deepen the knowledge on their nutritional quality. The aim of this study was to assess the nutritional quality of similar bakery products based on their fatty acids composition. Therefore, 5 of “Maria” cookies, 8 of plain salty cookies, 9 of coated chocolate cookies, 3 of brioche filled with chocolate, 3 of brioche with chocolate chips and 2 of French croissants were acquired in the major supermarkets chains from the Portuguese market. Fatty acid transesterification was performed using a methanolic solution of potassium hydroxide and n-heptane. Afterwards, the samples were analysed using a gas chromatograph with a flame ionization detector. Chromatographic separation of fatty acid methyl esters was performed using a Supelco® 2560 (100 m × 0.25 mm i.d., 0.25 µm film thickness) column, a split ratio of 50:1, an injection volume of 1 µL, and the injector and detector were kept at 240 ºC. Our results have shown, that one type of “Maria” cookies has a very different fatty acids distribution, with higher monounsaturated (MUFA) content, while all the other samples have a prevalence of SFA. For plain salty cookies group, the obtained results showed that 2 products have a clear distinct fat composition where MUFA were the major fatty acids, instead of SFA. Concerning sweet breads filled with chocolate, a higher content of polyunsaturated fatty acids was found, while the other samples had a higher content of SFA. With respect to the differences found between commercial and supermarket brands of similar foods, they were not sufficient to establish a relationship between brand/price/nutritional qualities. However, they allowed us to conclude that it is possible to produce similar foods, which are healthier with better nutritional quality.